Effectiveness of Solution-Focused Brief Counseling in Promoting Self-Disclosure among Junior High School Students: A Single Subject Design Study - Alvina Auliza Firjana; Dian Ari Widyastuti; Sri Tutur Martaningsih; Agungbudiprabowo; Hjh Salwa Dato Seri Setia Hj Mahalle (ILIN Institute Makassar, 2026)
Self-disclosure among junior high school students in Yogyakarta City is still low, requiring intervention to improve it. This study aims to determine the effectiveness of individual solution-focused brief counseling (SFBC) in improving self-disclosure in junior high school students. This study used a quantitative approach with a single subject design (SSD). The subjects in this study consisted of two junior high school students in Yogyakarta City selected using a purposive sampling technique. Data collection in this study used a self-disclosure scale and self-disclosure observation guidelines. Meanwhile, data analysis used visual data analysis using graphical representation. The results of the visual analysis showed an increase in self-disclosure, as indicated by the ABA design graph. Based on these findings, it can be concluded that individual solution-focused brief counseling is effective in improving self-disclosure in students. The results of this study can be a valuable reference for guidance and counseling teachers/counselors in implementing individual solution-focused brief counseling to help students increase their self-disclosure.